Multiple introductions, polyploidy and mixed reproductive strategies are linked to genetic diversity and structure in the most widespread invasive plant across Southern Ocean archipelagos - Mairal Pisa, Mario José; García‐Verdugo, Carlos; Le Roux, Johannes J.; Chau, John H.; van Vuuren, Bettine; Hui, Cang; Münzbergová, Zuzana; Chown, Steven L.; Shaw, Justine D. (Molecular Ecology, 2022)
Biological invasions in remote areas that experience low human activity provide unique opportunities to elucidate processes responsible for invasion success. Here we study the most widespread invasive plant species across the isolated islands of the Southern Ocean, the annual bluegrass, Poa annua. To analyse geographical variation in genome size, genetic diversity and reproductive strategies, we sampled all major sub‐Antarctic archipelagos in this region and generated microsatellite data for 470 individual plants representing 31 populations. We also estimated genome sizes for a subset of individuals using flow cytometry. Occasional events of island colonization are expected to result in high genetic structure among islands, overall low genetic diversity and increased self‐fertilization, but we show that this is not the case for P. annua. Microsatellite data indicated low population genetic structure and lack of isolation by distance among the sub‐Antarctic archipelagos we sampled, but high population structure within each archipelago. We identified high levels of genetic diversity, low clonality and low selfing rates in sub‐Antarctic P. annua populations (contrary to rates typical of continental populations). In turn, estimates of selfing declined in populations as genetic diversity increased. Additionally, we found that most P. annua individuals are probably tetraploid and that only slight variation exists in genome size across the Southern Ocean. Our findings suggest multiple independent introductions of P. annua into the sub‐Antarctic, which promoted the establishment of genetically diverse populations. Despite multiple introductions, the adoption of convergent reproductive strategies (outcrossing) happened independently in each major archipelago. The combination of polyploidy and a mixed reproductive strategy probably benefited P. annua in the Southern Ocean by increasing genetic diversity and its ability to cope with the novel environmental conditions. Depto. de Biodiversidad, Ecología y Evolución Fac. ...